DHL envirosolutions Australia: End-of-life management services for e-waste - DEMEESTER, Lieven (Institutional Knowledge at Singapore Management University, 2014)
Nichole Green, the Account Manager for Product Stewardship services at DHL Australia is reviewing regulatory changes that came into effect a month ago, in July 2013. These changes could potentially affect DHL Supply Chain’s Envirosolutions future business, particularly, its product stewardship services component. This was cause for concern as this service had been successful. Product stewardship services relied on an Australian Government regulatory framework built on the concept of Extended Producer Responsibility (EPR) – a policy that required producers to manage their product’s end-of-life segment by recycling a certain tonnage of electronic waste relative to their product tonnage imported into Australia. Envirosolutions was one of the approved providers of business-to-business logistics services for collecting and recycling waste on behalf of producers. In response to requests by ANZRP, a competing provider, the Australian regulator decided not to separate the categories of Computers and Televisions and to set combined recycling tonnage requirements. As the in-house expert on regulation, Green decides to bring this matter up with the Senior Director of Envirosolutions, Peter Bruce and the Operations and Compliance Manager, Mark Philips. Given the regulatory changes and the entry of a new provider, they need to analyse the regulatory and competitive environment to fine-tune their future strategy. With the initial success in Australia, DHL is also evaluating the feasibility of their success in product stewardship services in other Asian markets. This case can be discussed in classes on extended producer responsibility and reverse logistics. It is suitable for a course on sustainable operations or supply chain management. The case also lends itself to a discussion of the competitive strategy of a B2B service provider and can be used in a course on strategic management or competitive strategy. The case has been used successfully in junior and senior undergraduate classes as well as in post-graduate settings.